A novel design of vibration isolator with high and frequency dependent damping characteristics based on a Large Negative Poisson's Ratio (LNPR) structure. (1st March 2023) - Wu, Zhangming; Li, Hao; Kong, Xiangseng; Deng, Zehua
Abstract: In this paper, a biconcave-lens shaped structure with a large value of negative Poisson's ratio (LNPR) is proposed. By filling viscoelastic damping materials inside this LNPR structure, a novel vibration isolator with frequency dependent damping characteristics is designed. With this integrated design of negative Poisson's ratio structural element and viscoelastic materials, the compression and tension of the filled viscoelastic materials will be enlarged by the LNPR structure during a vibration process, which can effectively dissipate the vibrational energy. This proposed novel vibration isolator can achieve large damping characteristics and low vibration transmissibility, particularly when applying in micro-level vibration isolation. Finite element simulation is performed to predict the static and dynamic characteristics of this proposed novel vibration isolator, and characterize the hyperelastic and viscoelastic properties of the damping rubber. Finally, a vibration isolation platform using four proposed vibration isolators is established to perform frequency-sweep testings, with which our proposed design concept of this novel vibration isolator is demonstrated. Graphical abstract: Highlights: A biconcave-lens shaped metastructure with large negative Poisson's ratio (LNPR). A novel vibration isolator by filling viscoelastic materials into LNPR metastructure. This small size vibration isolator exhibits high damping at low frequency. This novel vibration isolator has adaptive damping characteristics.